Edukasi Diabetes Mellitus pada Ibu Hamil di Kelurahan Legok Kota Jambi - Dwi Kartika Pebrianti; Ratu Kusuma; Rahmi Dwi Yanti; Marnila Yesni (Prosiding Seminar Kesehatan Nasional, 2022)
Gestational diabetes mellitus (DM) is one of the cases of complications which is influenced by many factors including obesity, age, family history of DM, and history of giving birth to large babies. Gestational diabetes mellitus is a public health problem because this disease has a direct impact on the health of the mother and fetus. The impact caused by mothers with gestational diabetes mellitus is that mothers are at high risk of excess weight gain, the occurrence of preclampsia, eclampsia, cesarean section, and cardiovascular complications to maternal death. Health education is carried out for pregnant women to increase knowledge and it is hoped that efforts will be made to prevent the disease. The solution given is to provide health education to pregnant women about Pregnancy Diabetes Mellitus education in the Legok Village, the Working Area of the Putri Ayu Health Center, Jambi City, using the counseling method. After being given health education about gestational diabetes, out of 10 participants, 7 (70%) had good knowledge.